Web-Based Spatial Information System for Fisheries Potential in Cirebon Regency - Mubarak, Zaki (Cebong Journal, 2023)
Cirebon Regency, which is one of the easternmost regencies in West Java Province with an area of ​​989.70 Km2, a coastline of 54 Km and a pond area of ​​7,500.0 Ha, makes Cirebon Regency one of the potential areas for fishery business in West Java province. Based on fishery production development data for 2007, Cirebon district produced fishery production of 55,708 tons. However, in 2008 this value decreased to 52,342.40 tons or a decrease of 6.04%. (Marine and Fishery Service 2008: 35). The decline in production results is due to various factors including the lack of utilization of existing potential areas, lack of information, limited use of technology in the field of fisheries and so on. The lack of information about fishery resources causes a lack of optimal utilization of existing fishery resources, so it is necessary to use information technology such as the development of a spatial information system for fishery potential in Cirebon Regency. This information system displays potential fishery locations, for example pond locations, Fish Landing Bases and Fishery Product Processing Sites and is presented in spatial form and presented on a web-based basis, this will be easy to use, as well as the completeness of the the data presented can be used as a reference source for local governments in order to increase the potential of the existing fisheries sector.